Immune Dysregulation and Early Recurrence in Adhesive Intestinal Obstruction: A Retrospective Study - Alymkulov, Muratbek; Mambetov, Adyl; Uulu, Erbol Shamil; Alanbaev, Aibek; Mamatov, Niazbek; Abdiev, Allan; Zhumabekova, Altynai (Trends in Immunotherapy, 2025)
Adhesive intestinal obstruction (AIO) is a major complication of abdominal surgery, often leading to significant morbidity and a diminished quality of life. This study investigated the role of immune dysregulation in the development of early postoperative AIO and evaluated a multimodal strategy involving intraoperative lymphatic stimulation, mesenteric microirrigation, and immunoinflammatory biomarker monitoring to address adhesion-related complications in patients. This retrospective study included 38 patients who underwent surgery for acute AIO. Elevated levels of inflammatory markers, such as C-reactive protein, procalcitonin, interleukin-6, and tumor necrosis factor-alpha, have been observed in patients requiring reoperation due to early adhesion recurrence. Multivariable logistic regression analysis revealed that surgical history, adhesion severity, and elevated postoperative inflammatory markers were independent predictors of recurrence. Intraoperative lymphatic stimulation and postoperative mesenteric lavage with isotonic saline were performed to promote the removal of inflammatory mediators from the peritoneal cavity. Six of the seven patients who received this treatment showed symptom relief and decreased cytokine levels within 72 h. The study reported an early recurrence rate of 18.4% and a mortality rate of 2.6%. These findings suggest that monitoring inflammatory biomarkers after surgery could predict the risk of early adhesion recurrence, and employing a multimodal strategy targeting immune dysfunction during and after abdominal surgery may improve postoperative outcomes. The integration of immune-focused techniques, such as lymphatic stimulation and mesenteric lavage, could enhance standard surgical care by reducing inflammation and creating an environment that is less favorable for adhesion formation.